Ciprofloxacin Causes the Greatest Bacterial Community Variation in Swine Manure Composting - Song, Tingting; Zhu, Changxiong; Li, Binxu; Jiang, Kaiyang; Wang, Xuerong; Sardar, Muhammad Fahad; Xue, Sha; Huang, Yali; Li, Hongna (Frontiers in Environmental Science, 2021)
In this study, the influence of antibiotic types on the composition of the bacterial community structure was studied during aerobic composting with swine manure. Firmicutes (26.67%) and Chloroflexi (23.33%) were the most widely distributed phyla. Under all antibiotic treatments, the relative abundances of Bacillaceae, Streptosporangiaceae, Limnochordaceae, and Peptostreptococcaceae increased during the composting process. Moreover, norank_SBR1031, Planococcaceae, Thermomonosporaceae, Peptostreptococcaceae, Erysipelotrichaceae, Limnochordaceae, and Clostridiaceae_1 were the families showing the most significant differences across all treatments (p < 0.05). Principal co-ordinates analysis indicated that the family composition in the ciprofloxacin treatment significantly differed from the other treatments. The presence of ciprofloxacin increased both the abundance and diversity of the bacterial community (the Chao index changed from 588.44 to 680.17, and the Shannon index changed from 3.41 to 4.06) in the end of composting. Crocinitomicaceae dominated (relative abundance of 79.10%) among the unique families in the ciprofloxacin treatment. Network analysis indicated that ciprofloxacin altered the synergistic or competitive relationships between different families (norank_SBR1031 and Microscillaceae), leading to different bacterial community composition compared with other treatments. Further, a structural equation model showed that the C:N ratio was significantly negatively correlated with the bacterial community (λ = -0.869, p < 0.01), whereas pH showed a direct, significant positive relationship with the bacterial community (λ = 0.701, p < 0.01), especially in ciprofloxacin treatment. Overall, ciprofloxacin significantly influenced the physical and chemical properties of composting, altered the bacterial community structure. These findings have important implications for a better understanding of the effects of antibiotic types on bacterial community structure and the involved mechanisms during swine manure composting.